PROGRAMMING DETERMINATION OF THE STATE OF THE ELECTRIC THERMAL DEVICE FOR THE SYNTHESIS OF MICRO- AND NANOSTRUCTURAL COMPOSITE MATERIALS - Denysenko, Olexsander; Meschaninov, Sergiy (Scientific Works of Vinnytsia National Technical University, 2018)
Software-hardware complexes, intended for the synthesis of micro- and nanostructural composite materials as far as the control of energy release of electric thermal devices is concerned, refer to the control engineering and temperature regulation, applying electric means. The importance of the provision of rapid and efficient support of the computer-based diagnostics of the state and control of the energy release of the electric thermal devices of the software-hardware complexes in various energy conditions leads to the necessity of the determination of the set of the parameters which would comprehensively characterize instantaneous state of the electric thermal device at random moment of time as well as the set of the information factors, measured by means of the computer for fluctuating calculation of the parameters, determined on their base. The ratio of the instantaneous value of the thermally-dependent resistance of the electric heater to the internal resistance of the supply source is considered to be the determining parameter, regarding the formation of the range of the attainable values of the energy release and, as a result, the range of the attainable temperatures. To characterize the state of electric heater it is suggested to use the set of the instantaneous values of its relative values of thermal power and resistance. The set of the instantaneous values of these two parameters – electric voltages on the thermally- dependent resistance of the electric heater and on its serial connection with thermally-stabilized (reference) resistance is allocated as computer-registrated information factors for further computer-based determination of the electric heater state. The method of computer-based determination of the electric heater state exclusively on the base of the computer-based control of the supply source EMF and registration at the successive moments of time of simultaneously measured voltages on the thermally-dependent resistance of the electric heater and on its serial connection with thermostabilized resistance is suggested.